Pendekatan Tata Kelola Kolaboratif Dalam Pengembangan Produk Lokal UMKM di Desa Sukorambi Kecamatan Sukorambi Kabupaten Jember - Itok Wicaksono; Akbar Maulana; Binaridha Kusuma Ningtyas (Journal of Community Development, 2022)
Sukorambi Village, Sukorambi District, Jember Regency, which is rich in local potential, especially abundant natural resources and is very strategic in improving local product management (UMKM). and compete with other products, thus, development and empowerment in Sukorambi District is important to improve the quality, production and marketing of UMKM products in Sukorambi Village. Empowerment activities that are expected to help the development of UMKM and are sustainable are achieved so that the products marketed are able to compete with other products. Therefore, Solutions to Problems in developing local UMKM products in Sukorambi Village use a Collaborative Governance approach, which offers the concept of empowerment by involving various stakeholders or multidimensional, this concept places the community as the subject of empowerment so that the program to be carried out truly answers community problems, development UMKM local products involve the community, village government, and the private sector.